Greenhouse Gas Emissions and Crop Yields From Winter Oilseed Rape Cropping Systems are Unaffected by Management Practices - O’Neill, M.; Lanigan, G. J.; Forristal, P. D.; Osborne, B. A. (Frontiers in Environmental Science, 2021)
Winter oilseed rape is traditionally established via plough-based soil cultivation and conventional sowing methods. Whilst there is potential to adopt lower cost, and less intensive establishment systems, the impact of these on greenhouse gas emissions have not been evaluated. To address this, field experiments were conducted in 2014/2015 and 2015/2016 to investigate the effects of (i) crop establishment method and (ii) sowing method on soil greenhouse gas emissions from a winter oilseed rape crop grown in Ireland. Soil carbon dioxide, nitrous oxide and methane emission measurements were carried out using the static chamber method. Yield (t seed ha-1) and the yield-scaled global warming potential (kg CO2-eq. kg-1 seed) were also determined for each management practice. During crop establishment, conventional tillage induced an initially rapid loss of carbon dioxide (2.34 g C m-2 hr-1) compared to strip tillage (0.94 g C m-2 hr-1) or minimum tillage (0.16 g C m-2 hr-1) (P<0.05), although this decreased to background values within a few hours. In the crop establishment trial, the cumulative greenhouse gas emissions were, apart from methane, unaffected by tillage management when sown at a conventional (125 mm) or wide (600 mm) row spacing. In the sowing method trial, cumulative carbon dioxide emissions were also 21% higher when plants were sown at 10 seeds m-2 compared to 60 seeds m-2 (P<0.05). Row spacing width (125 mm and 750 mm) and variety (conventional and semi-dwarf) were found to have little effect on greenhouse gas emissions and differences in seed yield between the sowing treatments were small. Overall, management practices had no consistent effect on soil greenhouse gas emissions and modifications in seed yield per plant countered differences in planting density.